The Socio-Historical Background of 1 Peter in Relation to Αἰσχροκερδῶς and Κατακυριεύω form of Leadership in the Graeco-Roman Context (Global Journal of Human-Social Science, 2020)
The Graeco-Roman world has an indelible mark in shaping and influencing the background of the New Testament. The style of leadership in the context was more in the form of αἰσχροκερδῶς'greedy'and κατακυριεύω 'tyranny or lording over' (1 Peter 5:2-3) motives both from its political and religious perspectives. The purpose of the study is to demonstrate how such a background of the Graeco-Roman world shape and contributes to the writing of the epistle of 1 Peter, exclusively on the aspect of leadership in the church and Christian community. The study used the socio-historical method to show the condition and struggle of the early Christian amid greedy and tranny leaders in the Graeco-Roman context. The study, therefore, seeks to supply theologians as well as church leaders or Pastors with a better understanding of leadership from a socio-historical background of the Graeco-Roman world and how that can help in reading and handling issues of leadership in the New Testament, especially the epistle of 1 Peter.
Keywords: leadership; αἰσχροκερδῶς; κατακυριεύω; 1 peter; graeco-roman; emperor